Synthesis of novel diol modified chitosan and their enhanced selective adsorption behavior for germanium(Ⅳ). Issue 1 (February 2022) - Song, Xinlun; Chen, Hui; Gong, Liwen; Cui, Junshuo; Wang, Yuejiao; Wen, Siqi; Xing, Zhiqiang; Xiong, Ying
Abstract: Germanium (Ge) is an important semiconductor material, and its effective extraction and recovery is turning into progressively vital. However, high efficient recovery of Ge(IV) via convenient approach is remaining a challenge. Herein, an efficient adsorbent (HEMA-IDOI-CS) was prepared for recovering of Ge(IV) by grafting poly(hydroxyethyl methacrylate) (HEMA) and 3-chloro-1, 2-propanediol onto chitosan (CS). The steric effect of the o-hydroxyl groups is highly desirable to selectively chelate with tetrahedral Ge(IV), which greatly enhanced the efficiency of the CS-based materials. HEMA-IDOI-CS exhibited excellent adsorption performance at pH 3–8. The maximum capacity was 73.91 mg g −1 at pH 4, and the efficiency reached 99.26% at pH 4–6. In addition, HEMA-IDOI-CS exhibited good selectivity for Ge(Ⅳ) in the presence of Zn(II), Cu(II), Mn(II), Pb(II), As(III) and Fe(III). The kinetic data was well fitted with the pseudo-second-order kinetic model and the adsorption behavior is consistent with the Langmuir adsorption isotherm model. Moreover, the recovery rate of the adsorbent preserved 95% after four adsorption-elution cycles, demonstrating its good reusability. The adsorption performance of HEMA-IDOI-CS for Ge(Ⅳ) is much better than that of a lot other adsorbents previously reported. Graphical Abstract: ga1 Highlights: High efficient adsorbent for Ge(IV) was prepared from waste crab shells. Adsorbent with o-diol groups showed high capacity for Ge(IV) ( q e = 73.91 mg g −1 ). The adsorbent exhibited good selectivity and anti-interference ability for Ge(IV).